2015
DOI: 10.1002/lary.25516
|View full text |Cite
|
Sign up to set email alerts
|

Clinical analysis of drug‐induced sleep endoscopy for the OSA patient

Abstract: Patients who underwent UPPP ± T without DISE did not show a statistically significant difference in outcomes compared to the patients who underwent DISE with other procedures, including TORS. The TORS patients had increased total costs and length of stay that were statistically significant and had increased complications that were not statistically significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 23 publications
0
26
0
2
Order By: Relevance
“…46,47 Moreover, age was included in the logistic regression model to control for its influence. (ii) As a UA collapsibility evaluation method, DISE itself has some limitations, such as controversy about the reliability of observed obstructive sites, 48 that it might not improve surgical success rates, 49 and variable findings with prolonged observation time or different sedative drugs. 44,50 Dexmedetomidine was used for sedation, and differences in tongue base collapse related to propofol or midazolam use have already been identified.…”
Section: Discussionmentioning
confidence: 99%
“…46,47 Moreover, age was included in the logistic regression model to control for its influence. (ii) As a UA collapsibility evaluation method, DISE itself has some limitations, such as controversy about the reliability of observed obstructive sites, 48 that it might not improve surgical success rates, 49 and variable findings with prolonged observation time or different sedative drugs. 44,50 Dexmedetomidine was used for sedation, and differences in tongue base collapse related to propofol or midazolam use have already been identified.…”
Section: Discussionmentioning
confidence: 99%
“…The author concluded that D.I.S.E. does not improve the surgical success rate of surgery, but when more surgery is indicated, the rate of complications also increase [5].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, cine MRI and DISE both have been developed as dynamic airway evaluative tools and have overcome the limitation of the baseline muscle tone in the awake state that prevents visualization of upper airway collapse. However, both methods are significantly costly from a healthcare utilization standpoint due to their reliance on anesthesia and operating room resources …”
Section: Discussionmentioning
confidence: 99%
“…However, both methods are significantly costly from a healthcare utilization standpoint due to their reliance on anesthesia and operating room resources. 28,29 Computer simulation and upper airway modeling has been proposed as a method to overcome inherent limitations of clinical examination techniques in assessing patient sites of anatomic collapse. Further, this method is more cost-effective as a means of airway evaluation by avoiding anesthetic administration, and it offers the potential for subsite manipulation using computer software to determine an optimal airway configuration.…”
Section: Discussionmentioning
confidence: 99%